2004
DOI: 10.1165/rcmb.2004-0193oc
|View full text |Cite
|
Sign up to set email alerts
|

Acute Allergen-Induced Airway Remodeling in Atopic Asthma

Abstract: Studies in animals and in human atopic skin suggest that allergen challenge may activate acute tissue remodeling changes via transforming growth factor-beta pathways. We determined whether inhalational allergen challenge in subjects with mild asthma induces similar acute changes to the airway epithelial mesenchymal trophic unit (EMTU). Endobronchial mucosal biopsies obtained before and 24 h after challenge were examined by confocal microscopy for extracellular matrix deposition in the reticular basement membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 28 publications
8
90
0
2
Order By: Relevance
“…*P , 0.05. studies, TGF-b1, CTGF, and PAI-1 mRNA levels were all specifically enriched in the epithelial layer and not in the underlying smooth muscle. In addition, recent studies have shown activation of signaling pathways downstream of TGF-b receptor engagement in the bronchial epithelium in both animal models and biopsies from humans with asthma (15,(26)(27)(28)(29). Specifically, phospho-Smad 2, the activated receptor Smad, colocalizes with the epithelium in both antigen-challenged mice (including in this study) and humans with asthma.…”
Section: Discussionsupporting
confidence: 55%
“…*P , 0.05. studies, TGF-b1, CTGF, and PAI-1 mRNA levels were all specifically enriched in the epithelial layer and not in the underlying smooth muscle. In addition, recent studies have shown activation of signaling pathways downstream of TGF-b receptor engagement in the bronchial epithelium in both animal models and biopsies from humans with asthma (15,(26)(27)(28)(29). Specifically, phospho-Smad 2, the activated receptor Smad, colocalizes with the epithelium in both antigen-challenged mice (including in this study) and humans with asthma.…”
Section: Discussionsupporting
confidence: 55%
“…The level of P-Smad2 has been used as an indicator for TGF-␤ responsiveness (Smad2/3 dependent) in aortas and other tissues (Phipps et al, 2004;Liao and Laufs, 2005). The upregulation of VCAM-1 has been employed as a marker for early atherosclerotic lesions (Nakashima et al, 1998).…”
Section: Tgf-␤-induced Growth Inhibition Is Reversed By Cholesterolmentioning
confidence: 99%
“…26,27 Previous studies have shown that epithelial damage results in epithelial cells releasing pro-inflammatory factors such as IL-1 and tumor necrosis factor-a. 28 These factors in turn recruit and stimulate mast cells to release various factors including IL-10.…”
Section: Discussionmentioning
confidence: 99%